Harnessing red grape pomace extract for sustainable broad-spectrum photoprotection in a reconstructed human epidermis model - Smeriglio, Antonella; Mangano, Marta; Ingegneri, Mariarosaria; La Neve, Annarita; Brenna, Chiara; Mastracci, Luca; Merlino, Francesco; Tonon, Giancarlo; Bosco, Diego; Trombetta, Domenico (Frontiers in Pharmacology, 2026)
Red grape pomace, a major by-product of the winemaking industry, represents a sustainable source of bioactive polyphenols with high nutraceutical and cosmetic potential. In this study, a standardized grape pomace extract (GPE) was developed from quality-controlled dried pomace, compliant with European Pharmacopoeia requirements for heavy metals, microbiological purity, and residual moisture. Phytochemical profiling by LC-DAD-ESI-MS/MS revealed a complex composition dominated by anthocyanins—primarily malvidin-3-O-glucoside—alongside lignans, stilbenes, and flavonols. The extract showed a high total phenolic content (2.64 g GAE/100 g) and exhibited strong, concentration-dependent antioxidant activity, with the highest efficacy in FRAP and ORAC assays, and significant anti-inflammatory effects in protein denaturation and protease inhibition tests. GPE demonstrated excellent photochemical stability and was incorporated into a lipid-based cosmetic formulation (SS + GPE) to assess its safety and photoprotective efficacy in a reconstructed human epidermis (RHE) model exposed to UVA (26 J/cm2) and UVB (1.5 J/cm2) radiation. Both GPE and SS + GPE treatments markedly reduced ROS, NO, and IL-1α production (up to 60%–65% reduction vs. irradiated control) while maintaining cell viability above 90%. Histological analysis further confirmed the structural protection of the epidermis, showing fewer dyskeratotic cells, restored intercellular cohesion, and normalization of keratinization. Overall, these results demonstrate that GPE is a safe, photostable, and multifunctional bioactive extract capable of counteracting UV-induced oxidative and inflammatory damage. This study provides a comprehensive and sustainable strategy for the upcycling of red grape pomace into high value dermocosmetic formulations with proven broad-spectrum photoprotective efficacy.